2017
DOI: 10.1098/rstb.2016.0123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of conservation management of landscapes and vertebrate communities on Lyme borreliosis risk in the United Kingdom

Abstract: Landscape change and altered host abundance are major drivers of zoonotic pathogen emergence. Conservation and biodiversity management of landscapes and vertebrate communities can have secondary effects on vector-borne pathogen transmission that are important to assess. Here we review the potential implications of these activities on the risk of Lyme borreliosis in the United Kingdom. Conservation management activities include woodland expansion, management and restoration, deer management, urban greening and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 137 publications
(216 reference statements)
0
41
0
2
Order By: Relevance
“…Nevertheless, although roe deer are not considered competent reservoir hosts for Borreliella spp. because they do not develop systemic infection and transmit the infection to susceptible ticks (Kjelland et al, 2011;Sprong et al, 2012), their role as host for ticks makes them central to the geographical distribution of ticks and transmitted agents such as LB spirochetes (Millins et al, 2017). Indeed, several studies have shown a positive relationship between both cervid and tick populations and therefore the risk to acquire LB (Kjelland et al, 2011;Sprong et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, although roe deer are not considered competent reservoir hosts for Borreliella spp. because they do not develop systemic infection and transmit the infection to susceptible ticks (Kjelland et al, 2011;Sprong et al, 2012), their role as host for ticks makes them central to the geographical distribution of ticks and transmitted agents such as LB spirochetes (Millins et al, 2017). Indeed, several studies have shown a positive relationship between both cervid and tick populations and therefore the risk to acquire LB (Kjelland et al, 2011;Sprong et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Stage-specific transmission dynamics has also been shown to impact disease dynamics [88]. Incorporating vector populations into these null models and how these respond to changes in habitat area and host availability in these models will be an essential next step [89,90].…”
Section: Discussionmentioning
confidence: 99%
“…Kilpatrick et al [24] synthesize knowledge on Lyme disease ecology and describe the data gaps that have created controversy in the Lyme disease system. In bringing together authors from disparate viewpoints and diverse places, they lay the groundwork for future research to resolve major controversies and improve control.…”
Section: Topics Addressed In This Issuementioning
confidence: 99%